Hubungan Dokter dengan Pasien Dalam Bidang Kesehatan - Bing Waluyo (Faculty of Law, Universitas Wijayakusuma, 2023)
Abstract The relationship between doctors and patients begins with a vertical, paternalistic relationship pattern, which is based on the principle of father knows best, which gives birth to a paternalistic relationship. The position/position of the doctor and the patient are not equal, namely the position of the doctor is considered higher than the patient, because the doctor is considered to know best about all kinds of diseases and how to cure them, while the patient is considered to know nothing about the disease and he submits it completely to the doctor. Doctors are placed as patrons (protectors) and patients are placed as clients (protected people). Then, in its development, the vertical, paternalistic relationship pattern shifted to a horizontal, contractual relationship pattern. This relationship gives birth to a horizontal contractual legal aspect which is inspanningsverbintenis which is a legal relationship between two legal subjects (patients and doctors) who are of equal status, giving rise to rights and obligations for the parties concerned. This legal relationship does not promise anything (healing or death) because the object of the legal relationship is the maximum effort made by the doctor carefully and with tension based on his knowledge and experience in treating illnesses to cure the patient's illness. Keywords: Juridical Review, Relationship, Doctor and Patient, Health Sector. Abstrak Hubungan antara dokter dengan pasien bermula pada pola hubungan vertikal paternalistik, yang bertolak pada prinsip father knows best, yang melahirkan hubungan yang bersifat paternalistik. Kedudukan/posisi dokter dengan pasien tidak sederajat yaitu kedudukan dokter dianggap lebih tinggi daripada pasien, karena dokter dianggap paling tahu tentang segala macam penyakit dan cara penyembuhannya, sedang pasien dianggap tidak tahu apa-apa tentang penyakit.dan dia menyerahkan sepenuhnya kepada dokter. Dokter di tempatkan sebagai patron (pelindung) dan pasien di tempatkan sebagai klien (orang yang dilindungi). Kemudian pada perkembangannya pola hubungan yang vertikal paternalistik, bergeser menjadi pola hubungan horizontal kontraktual. Hubungan ini melahirkan aspek hukum horizontal kontraktual yang bersifat inspanningsverbintenis yang merupakan hubungan hukum antara dua subyek hukum (pasien dan dokter) yang berkedudukan sederajat, melahirkan hak dan kewajiban bagi para pihak yang bersangkutan. Hubungan hukum ini tidak menjanjikan sesuatu (kesembuhan atau kematian) karena obyek dari hubungan hukum itu berupa upaya maksimal yang dilakukan oleh dokter secara hati-hati dan penuh ketegangan berdasarkan ilmu pengetahuan dan pengalamannya dalam menangani penyakit untuk menyembuhkan penyakit pasien. Kata Kunci: Tinjauan Yuridis, Hubungan, Dokter dengan Pasien, Bidang Kesehatan.